The Evolution of Geospatial Aspects in the Law on the Establishment of New Regions (Autonomy) Pre and Post Broad Autonomy in Indonesia - Farouki Dinda Rassarandi; Helik Susilo; Kariyono Kariyono; Khairul Fajri; Febrian Fitryanik Susanta (Politeknik Negeri Batam, 2019)
Expansion or establishment of new regions (Provinces, Regencies/Cities) is a consequence of the politics of decentralization implemented in Indonesia. The development of decentralization in Indonesia underwent fundamental changes after the reformation in 1998. Inception of UU No 22 tahun 1999 concerning regional government has given a new color to the administration of government in Indonesia or what is called broad autonomy. Restructuring regional governments that provide discretion in the form of broader authority in running their government in accordance with regional needs has created many implications for the region, one of which is stretching and the spirit of the region to bloom. In determining the boundaries of forming new regions, the geospatial aspect is an important and strategic aspect. Problems related to geospatial aspects such as maps of regional boundaries, area size, etc are issues that need to be clearly defined and calculated in the new (autonomous) regional (Province, Regency/City) determination. But in fact the law on the formation or establishment of regions in the period 1950-1999 on the geospatial aspect did not become an important part so that it caused problems later which could potentially trigger social conflicts such as regional boundary disputes. Post-reformation, the development of the role of the geospatial aspects has evolved a little more advanced, such as the existence of regional boundary maps in the appendix to the law on the formation or expansion of new regions, such as UU No 7 tahun 2002, UU No 2 tahun 2003, and others. However, there is still something that must be evaluated regarding the map in the attachment to be in accordance with the geospatial rules. A very progressive development in terms of the geospatial aspect is in UU No 20 tahun 2012 concerning the formation of the Kalimantan Utara province that utilizes geospatial data properly